# ALGEBRAIC IDENTITIES WORKSHEET

1. Expand : (3x + 4y)2

2. Expand : (2p - 3q)2

3. Expand : (5x + 4y)(5x - 4y)

4. Expand : (m + 3)(m + 5)

5. Expand : (m - 7)(m + 2)

6. Expand : (a - b + c)2

7. Expand : (a + b - c)2

8. Expand : (a - b - c)2

9. Expand : (2x + 3y + 4z)2

10. Find the area of square whose side length is (3p + 2q - 4r)

11. Expand (x + 4)(x + 5)(x + 6)

12. Expand (3x - 1)(3x + 2)(3x - 4)

13. Expand (x - y)3

14. Expand (5a - 3b)3

15. Find the product of :

(2x + 3y + 4z)(4x2 + 9y2 + 16z2 - 6xy - 12yz - 8xz)

16. Evaluate : 103 - 153 + 53.

(3x + 4y)2

We have

(a + b)2 = a2 + 2ab + b2

Substitute a = 3x and b = 4y.

(3x + 4y)2(3x)2 + 2(3x)(4y) + (4y)2

32x2 + 2(3x)(4y) + 42y2

= 9x2 + 24xy + 16y2

(2p - 3q)2

We have

(a - b)2 = a2 - 2ab + b2

Substitute a = 2p and b = 3q.

(2p - 3q)2 = (2p)2 - 2(2p)(3q) + (3q)2

= 22p2 - 12pq + 32q2

= 4p2 - 12pq + 9q2

(5x + 4y)(5x - 4y)

We have

(a + b)(a - b) = a2 - b2

Substitute a = 5x and b = 4y.

(5x + 4y)(5x - 4y) = (5x)2 - (4y)2

52x2 - 42y2

= 25x2 - 16y2

(m + 3)(m + 5)

We have

(x + a)(x + b) = x2 + (a + b)x + ab

Substitute x = m, a = 3 and b = 5.

(m + 3)(m + 5) = m2 + (3 + 5)m + (3)(5)

= x2 + 8m + 15

(m - 7)(m + 2)

We have

(x + a)(x + b) = x2 + (a + b)x + ab

Substitute x = m, a = -7 and b = 7.

(m - 7)(m + 2) = m2 + (-7 + 2)m + (-7)(2)

= m2 - 5m - 14

(a - b + c)2

We have

(a + b + c)2 = = a2 + b2 + c+ 2ab + 2bc + 2ac

Replace 'b' by '-b'.

(a + (-b) + c)2 = = a2 + (-b)2 + c+ 2a(-b) + 2(-b)c + 2ac

(a - b + c)2 = = a2 + b2 + c- 2ab - 2bc + 2ac

(a + b - c)2

We have

(a + b + c)2 = = a2 + b2 + c+ 2ab + 2bc + 2ac

Replace 'c' by '-c'.

(a + b + (-c))2 = = a2 + b2 + (-c)+ 2ab + 2b(-c) + 2a(-c)

(a + b + (-c))2 = = a2 + b2 + c+ 2ab - 2bc - 2ac

(a - b - c)2

We have

(a + b + c)2 = = a2 + b2 + c+ 2ab + 2bc + 2ac

Replace 'b' by '-b' and 'c' by '-c'.

(a + (-b) + (-c))2 = = a2 + (-b)2 + (-c)+ 2a(-b) + 2(-b)(-c) + 2a(-c)

(a - b - c)2 = = a2 + b2 + c- 2ab + 2bc - 2ac

(2x + 3y + 4z)2

We have

(a + b + c)2 = = a2 + b2 + c+ 2ab + 2bc + 2ac

Substitute a = 2x, b = 3y and c = 4z.

(2x + 3y + 4z)2 = (2x)2 + (3y)2 + (4z)+ 2(2x)(3y) + 2(3y)(4z) + 2(2x)(4z)

= 22x2 + 32y2 + 42z+ 12xy + 24yz + 16xz

= 4x2 + 9y2 + 16z+ 12xy + 24yz + 16xz

Area of Square :

= side x side

= (3p + 2q - 4r)(3p + 2q - 4r)

= (3p + 2q - 4r)2

We know that

(a + b + c)2 = = a2 + b2 + c+ 2ab + 2bc + 2ac

Substitute a = 3p, b = 2q and c = -4r.

(3p + 2q + (-4r)2 = (3p)2 + (2q)2 + (-4r)+ 2(3p)(2q) + 2(2q)(-4r) + 2(3p)(-4r)

= 9p2 + 4q2 + 16r+ 12pq - 16qr - 24pr

Therefore, Area of Square = [9p2 + 4q2 + 16r+ 12pq - 16qr - 24pr] square units.

(x + 4)(x + 5)(x + 6)

We know that

(x + a)(x + b)(x + c) = x3 + (a + b + c)x2 + (ab + bc + ac)x + abc

Substitute a = 4, b = 5 and c = 6.

(x + 4)(x + 5)(x + 6) = x3 + (4 + 5 + 6)x2 + [(4)(5) + (5)(6) + (4)(6)]x + (4)(5)(6)

= x3 + 15x2 + (20 + 30 + 24)x + 120

= x3 + 15x2 + 74x + 120

(3x - 1)(3x + 2)(3x - 4).

We know that

(x + a)(x + b)(x + c) = x3 + (a + b + c)x2 + (ab + bc + ac)x + abc

Substitute x = 3x, a = -1, b = 2 and c = -4.

(3x - 1)(3x + 2)(3x - 4)

= (3x)3 + (-1 + 2 - 4)(3x)2 + [(-1)(2) + (2)(-4) + (-1)(-4)](3x) + (-1)(2)(-4)

= 27x3 + (-3)(9x2) + (-2 - 8 + 4)(3x) + 8

= 27x3 - 27x2 + (-6)(3x) + 8

= 27x3 - 27x2 - 18x + 8

(x - y)3

We know that

(x + y)3 = x3 + 3x2y + 3xy2 + y3

Replace 'y' by '-y'.

(x + (-y))3 = x3 + 3x2(-y) + 3x(-y)2 + (-y)3

= x3 - 3x2y + 3xy2 - y3

or

=  = x3 - 3xy(x - y) - y3

(5a - 3b)3

We know that

(x + y)3 = x3 + 3x2y + 3xy2 + y3

We know that

(x + y)3 = x3 + 3x2y + 3xy2 + y3

Substitute x = 5a, and y = -3b.

(5a - 3b)3 = (5a)3 + 3(5a)2(-3b) + 3(5a)(-3b)2 + (-3b)3

= 53a3 + 3(25a2)(-3b) + 3(5a)(9b2) + (-27b3)

= 125a3 - 225a2b + 135ab2 - 27b3

(2x + 3y + 4z)(4x2 + 9y2 + 16z2 - 6xy - 12yz - 8xz)

We know that

(a + b + c)(a2 + b2 + c2 - ab - bc - ac) = a3 + b3 + c3 - 3abc

Substitute a = 2x, b = 3y and c = 4z.

(2x + 3y + 4z)(4x2 + 9y2 + 16z2  - 6xy - 12yz - 8xz)

= (2x)3 + (3y)3 + (4z)3 - 3(2x)(3y)(4z)

= 8x3 + 27y3 + 64z3 - 72xyz

103 - 153 + 53

We know that, If (a + b + c) = 0, then a3 + b3 + c3 = 3abc.

If a = 10, b = -15 and c = 5, then

a + b + c = 10 - 15 + 5 = 0

Therefore,

103 + (-15)3 + 53 = 3(10)(-15)(5)

103 - 153 + 5= -2250

## Recent Articles

1. ### Finding Range of Values Inequality Problems

May 21, 24 08:51 PM

Finding Range of Values Inequality Problems

2. ### Solving Two Step Inequality Word Problems

May 21, 24 08:51 AM

Solving Two Step Inequality Word Problems